Вплив препаратiв дрiжджової РНК на репродуктивну здатнiсть мишей - Ткачук, З.Ю.; Яковенко, Т.Г.; Семерникова, Л.I.; Шаповал, С.О.; Артеменко, В.С. (Видавничий дім "Академперіодика" НАН України, 2007)
It is demonstrated that pellets of yeast RNA in optimal concentrations considerably increase the ability of females over 8 months to become pregnant; at the same time, the high indicators of young 5-month-old mice of BALB line are not influenced. The compound reliably increases the average number of baby mice in brood, does not influence the growth of sucker mice, and, at the same time, reliably influences the number of offsprings from young females. Various supplements in RNA pellets reliably increase the average number of baby mice in brood and the number of offsprings from young females.